Mining Hospital Processes: A Case Study - Kim, Chae-Young; Kang, Ha-Na; Hwang, Hyun-Seok (International Journal of Psychosocial Rehabilitation, 2020)
The growing demand for medical services is raising in healthcare. In addition, due to the development of data information systems, all information related to the medical care process in hospitals is stored and attempts to analyze it are increasing. Accordingly, this study aims to comprehend the medical care process by utilizing process mining technique. The data was collected over three months, and the data consist of information on the medical care process of patients. To identify the overall process, the data was classified by age, gender, medical department and payment type. Contrary to expectations that there would be differences between the two activities (Test Registration, Tests) by classification, the difference was not significant. However, under the activities ‘general payment’ and ‘unmanned payment’, there was significant difference. Through the analysis, this study provides more efficient payment type was identified in the medical care processes.